Overview of early cretaceous gold mineralization in the orogenic belt of the eastern margin of the Siberian craton: geological and genetic features - Goryachev, Nikolay; Fridovsky, Valery (Frontiers in Earth Science, 2024)
The giant Verkhoyansk-Kolyma gold province, producing more than∼ 3700 t of gold, is one of the most important metallogenic provinces for orogenic gold deposits in the world. The province is located on the eastern margin of the Siberian craton. The main types here are multistage orogenic Au-As and orogenic-like Au-Sb types of mineralization, related to the Late Jurassic-Early Cretaceous metallogeny and the evolution of the convergent margin. These deposits were formed in the environment of late orogeny during two metallogenic stages—the Late Jurassic-Early Cretaceous collision-related (early stage/stage one, 135–150 Ma) and the Early Cretaceous subduction-related (late stage/stage two 114–130 Ma). The common features, differences and genetic nature of the deposits of these two metallogenic stages have been debated for a long time. To improve the understanding of these problematic issues and the genesis of deposits, and control over them by the mantle lithosphere, we consider here the Early Cretaceous orogenic belts of the eastern margin of the Siberian craton. Orogenic belts are related to the development of the paleo-Arctic and paleo-Pacific margins of Siberia. The tectonic, geochronological, mineralogical and geochemical specificity of the deposits of the orogenic belts are shown. A regional metallogenic overview of gold deposits is performed using data on the age of mineralization and the isotopic composition of sulfur sulfides. A preliminary model of the origin of late stage mineralization is proposed in connection with the processes of the Okhotsk-Koryak orogenic belt formation. Increased concentrations of siderophilic and chalcophilic elements, the Ni, Bi minerals presence in the ores, relatively high fineness of gold, predominance of juvenile sulfur in the isotopic composition of sulfide sulfur, аnd the control by large trans-crustal faults as well as spatial and chronological association with initial (dike) magmatism indicate mantle sources of ore fluids. This mineralization within the orogenic belts of the eastern margin of the Siberian craton assumingly appeared due to dehydration of the submerged slab and local upwelling in the mantle in the rear of the active continental margin. The possibility of the gold-bearing fluids existence in such conditions is estimated. The metallogenic specific nature of collision-related and subduction-related orogenic Au is defined. The proposed model can be useful for the analysis of polychronous orogenic Au-As and orogenic-like Au-Sb metallogeny of orogenic belts on craton margins globally.